Activated Niobium and Tantalum Imido Complexes: From Tuneable Polymerization to Selective Ethylene Dimerization Systems. Issue 6 (20th February 2019) - Messinis, Antonis M.; Batsanov, Andrei S.; Howard, Judith A. K.; Hanton, Martin J.; Dyer, Philip W.
Abstract: The niobium and tantalum imido complexes [CpMCl2 (NDipp)], [MCl3 (NR)(dme)] (R= t Bu, Ph, 2, 6‐ i Pr2 C6 H3 (Dipp), and Mes), and [TaCl3 (NDipp)(tmeda)] were tested in combination with EtAlCl2 for the dimerization of ethylene. The niobium systems afforded dimers or polymers, depending on the nature of the imido ligand, with overall productivities in the range 720 to 13, 720 (mol C2 H4 )(mol Nb) −1 . The nature of the polyethylene produced (LDPE or HDPE) depended on the imido ligand and the niobium concentration at which catalysis was run. In contrast, the tantalum/dme systems all mediated ethylene dimerization with productivities of up to 4, 503 (mol C2 H4 )(mol Ta) −1, with overall selectivities to butenes of between 73–81 wt %; selectivity within the dimer fraction to 1‐butene was in the range 72 to 100 %. The productivity of [TaCl3 (NDipp)(tmeda)] was six times higher than that of its dme‐bearing counterpart, but at the cost of selectivity to 1‐butene. For the tantalum imido‐mediated ethylene dimerization the composition of the product slate formed is indicative of a metallacyclic mechanism being operative. Abstract : Tuning catalysis : Activation of niobium mono(imido) complexes with EtAlCl2 affords catalysts that produce dimers or polyethylene depending on the nature of the imido substituent. In contrast, the analogous tantalum systems, irrespective of the organoimido motif, mediate predominantly ethylene di‐ and tri‐merisation with overall selectivities to butenes of between 73.0–80.7 wt % and selectivity within the dimer fraction to 1‐butene in the range 72.4 to 100 %.